PENERAPAN METODE KONTRASEPSI UNTUK PENINGKATAN PENGETAHUAN WANITA USIA SUBUR DI DESA DUMU 1 SIDODADI KECAMATAN SIBIRU BIRU - Hutabarat, Vitrilina -; Siregar, G.F. Gustina; Sriwahyuni, Eka (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
Family planning is a government program designed to balance the needs of the population. Planning for the number of families through restrictions can be applied when using contraception, both hormonal and non-hormonal contraception. Some women of childbearing age in Desa Dumu I of Sidodadi Village experience a low level of knowledge about contraceptives. This field practice learning activity aims to increase the knowledge of women of childbearing age through counseling to increase the knowledge of women of childbearing age about contraceptive methods. Counseling was carried out on March 15, 2023. Counseling was carried out by the presentation method and giving leaflets about types of contraceptives, things that are dangerous if women of childbearin1. g age do not use contraception.